Instruments for quality of life assessment in individuals with human papillomavirus - Natália Maria Vieira Pereira-Caldeira; Fernanda Maria Vieira Pereira-Ávila; Maria Cristina Mendes de Almeida-Cruz; Lílian Andreia Fleck Reinato; Renata Karina Reis; Elucir Gir
ABSTRACT Objective: To identify scientific evidence on quality of life measurement instruments used in individuals with infections caused by human papillomavirus. Method: This was an integrative review carried out from April 1995 to March 2017 in the LILACS, SciVerse Scopus, ISI Web of Science, CINAHL, and PubMed databases. The controlled descriptors adopted were: Infecções por Papilomavirus; Qualidade de Vida; Papillomavirus Infections; and Quality of Life. Results: Of the 416 articles found, 12 were selected. Thirteen different types of instruments to evaluate the quality of life of individuals with human papillomavirus were identified, in that nine were generic and four specific. Conclusion: Different generic and specific instruments were used to evaluate the quality of life of individuals with human papillomavirus, which means no consensus or preference among the studies was identified. However, a lack of use of specific instruments to evaluate this construct in this population was observed.